Analisis keunggulan dan kekurangan Problem Based Learning (PBL) dalam Pembelajaran Pendidikan Agama Islam - Muhammad Ainul Wildan; Muhammad Adil Amrullah; Nadiah Salma Fairuzah; M. Yunus Abu Bakar (Mathematics Education Study Program, 2025)
This study aims to analyze the advantages and disadvantages of Problem Based Learning (PBL) in Islamic Religious Education (PAI). Using a descriptive qualitative approach with library research methods, this research analyzes various relevant literature sources. The findings indicate that PBL offers significant advantages in the context of PAI, including the development of critical, analytical, and reflective thinking skills, strengthening moral and spiritual responsibility, fostering collaboration, and increasing student learning motivation through solving authentic, contextual problems. However, the implementation of PBL in PAI also faces several challenges, such as the low pedagogical readiness of teachers in designing problem scenarios aligned with Islamic values, limitations in time and learning facilities, and resistance to the shift from traditional teaching paradigms. The success of PBL in PAI heavily depends on the teacher's ability as a facilitator to integrate modern constructivist approaches with the principles of Islamic pedagogy, such as tarbiyah, ta'dib, and muhasabah. This study concludes that PBL is a relevant and effective learning model for PAI, provided there is adequate support for teacher competency development and learning infrastructure.